Parental Anxiety’s Relationship to Children’s Fear and Behaviors During the Pandemic - Ümran Çevik Güner; Duygu Ayar (Çocuk Dergisi)
Objective: The various restrictions applied during the pandemic have led to children as well as adults and individuals in the role of parents being deprived of social interactions and friendship. For this reason, certain mental and behavioral changes are observable in both parents and children. The aim of this research is to examine the relationship parental anxiety has to children’s fears and behaviors during the pandemic. Material and Methods: This is a cross-sectional descriptive relational study conducted between February and June 2021 in Turkey with 264 children between the ages of 4-10 and their parents. Data were collected using a sociodemographic form, the Children’s Daily Routines During the Pandemic Form, the Coronavirus Anxiety Scale-Short Form, and the Child Fear Scale. Numerical, percentage, means, and Pearson correlation analyses were used to analyze the data. Results: Parents’ mean score on the Coronavirus Anxiety Scale-Short Form was 13.29±2.80; children’s mean score on the overall Children’s Fear Scale was 3.35±1.47, and a significant positive relationship was found between them. In addition, a correlation was found between parents’ coronavirus anxiety and children’s fear levels during the pandemic, with positive relationships found among children’s nutritional behavior, body weight change, sleep change, sleeping late, nightmares, increased use of technological devices, arguing with family members, and wanting to play outside the home. Conclusion: The study has determined parents’ coronavirus anxiety levels and children’s fear levels to be above average. The increase in parents’ anxiety about COVID was also found to increase children’s fear levels. Meanwhile, behavioral and emotional differences were determined to have occurred in children during the pandemic.